Selective decrease of cholinergic signaling from pedunculopontine and laterodorsal tegmental nuclei has little impact on cognition but markedly increases susceptibility to stress. Issue 6 (11th March 2019) - Janickova, Helena; Kljakic, Ornela; Rosborough, Kaie; Raulic, Sanda; Matovic, Sara; Gros, Robert; Saksida, Lisa M.; Bussey, Timothy J.; Inoue, Wataru; Prado, Vania F.; Prado, Marco A. M.
ABSTRACT: The pedunculopontine tegmental nucleus (PPT) and laterodorsal tegmental nucleus (LDT) are heterogeneous brainstem structures that contain cholinergic, glutamatergic, and GABAergic neurons. PPT/LDT neurons are suggested to modulate both cognitive and noncognitive functions, yet the extent to which acetylcholine (ACh) signaling from the PPT/LDT is necessary for normal behavior remains uncertain. We addressed this issue by using a mouse model in which PPT/LDT cholinergic signaling is highly decreased by selective deletion of the vesicular ACh transporter ( VAChT ) gene. This approach interferes exclusively with ACh signaling, leaving signaling by other neurotransmitters from PPT/LDT cholinergic neurons intact and sparing other cells. VAChT mutants were examined on different PPT/LDT‐associated cognitive domains. Interestingly, VAChT mutants showed no attentional deficits and only minor cognitive flexibility impairments while presenting large deficiencies in both spatial and cued Morris water maze (MWM) tasks. Conversely, working spatial memory determined with the Y‐maze and spatial memory measured with the Barnes maze were not affected, suggesting that deficits in MWM were unrelated to spatial memory abnormalities. Supporting this interpretation, VAChT mutants exhibited alterations in anxiety‐like behavior and increased corticosterone levels after exposure to the MWM, suggesting altered stress response. Thus, PPT/LDT VAChT‐mutant mice present little cognitive impairment per se, yet they exhibit increased susceptibility to stress, which may lead to performance deficits in more stressful conditions.—Janickova, H., Kljakic, O., Rosborough, K., Raulic, S., Matovic, S., Gros, R., Saksida, L. M., Bussey, T. J., Inoue, W., Prado, V. F., Prado, M. A. M. Selective decrease of cholinergic signaling from pedunculopontine and laterodorsal tegmental nuclei has little impact on cognition but markedly increases susceptibility to stress. FASEB J. 33, 7018–7036 (2019). www.fasebj.org